The Impact of Academic Stress on Students' Mental Health: Coping Interventions Based on Virtual Reality Technology - Alma Syifa Maulidina; Thalita Syifa Fatimah (International Journal of Psychology and Health Science, 2024)
Academic stress is a common issue faced by university students, particularly in major cities like Jakarta, and often has a negative impact on their mental health. This study aims to evaluate the effectiveness of Virtual Reality (VR) technology as an innovative coping strategy to reduce academic stress and improve students' mental health. The study utilized a quasi-experimental design involving 60 students from various universities in Jakarta who met the inclusion criteria, which included having moderate to high levels of academic stress. Participants were randomly divided into two groups: an experimental group (using VR intervention) and a control group (using conventional coping strategies). Data were collected using the Student-Life Stress Inventory (SSI) to measure academic stress levels and the Depression Anxiety Stress Scales (DASS-21) to assess mental health, at both pre-test and post-test stages. The results showed that the experimental group receiving the VR intervention experienced a significant reduction in academic stress levels (with an effect size of 1.86) and an improvement in mental health (with an effect size of 2.02), compared to the control group, which showed smaller changes. These findings support the hypothesis that VR-based coping interventions are more effective than conventional coping strategies in reducing academic stress and improving students' mental health. These results have practical implications for educational institutions to consider incorporating VR technology into student mental health support programs. The study suggests using VR as an engaging and relevant coping method for the tech-savvy student generation.